Screening of Anaerobic Germination Rice Genotypes in Nepal - Tripathi, Santosh Raj; Dhakal, Krishna Hari; Ghimire, Surya Kanta; Dixit, Salabh; Yadav, Ram Baran; Subedi, Sushil Raj (International Journal of Applied Sciences and Biotechnology, 2023)
Poor germination has been the main obstacles to the widespread adoption of rainfed lowland rice production due to the saturated state of the soil, . In order to produce rice types appropriate for direct seeded culture, the current experiment was conducted to find rice with anaerobic germination tolerance. The screening techniques of the tray method were used to assess the anaerobic germination tolerance of 402 different rice genotypes. Under anaerobic conditions, the genotypes 10 genotypes namely, IR 129077:1-1-6-8-B, IR 129077:1-1-6-9-B, IR 129077:2-1-16-8-B, IR 129077:1-1-36-5-B, IR 129077:1-1-41-7-B, IR 129077:1-1-46-6-B, IR 129077:2-1-17-6-B, IR 129077:1-1-31-5-B, IR 129077:1-1-39-8-B, IR 129077:2-1-13-7-B, IR 129077:2-1-17-7-B and IR 129077:2-1-28-7-B recorded the highest germination percentages (> 80%). Under anaerobic germination, the recorded coleoptile length for all genotypes ranged from 0.50 to 10.6 cm. The best performing genotypes were chosen for genotyping using previously published SSR markers based on the screening results. On QTL analysis, anaerobic germination QTL (qAG) present on Chromosome number 11 and chromosome 12 for higher germination and QTL (qCL) on chromosome 12 for longer coleoptile. Int. J. Appl. Sci. Biotechnol. Vol 11(2): 78-84.